Molecular mechanism of Ras-related protein Rab-5A and effect of mutations in the catalytically active phosphate-binding loop. Issue 1 (2nd January 2017) - Khan, Faez Iqbal; Aamir, Mohd.; Wei, Dong-Qing; Ahmad, Faizan; Hassan, Md. Imtaiyaz
Abstract : Ras-related protein (Rab-5a) is primarily involved in the regulation of early endosome fusion during endocytosis and takes part in the budding process. During GTP hydrolysis, Rab5a was spotted in the cytoplasmic side of early endosomes in association with the GTP. Previous study suggested that the substitution of alanine with proline at position 30 of Rab5a reduces the GTPase activity around 12-fold, while, with arginine substitution stimulates the intrinsic GTP hydrolysis by 5-fold. Most of the other substitutions at this position show a little or no effect on the GTPase activity. In this paper, structure analysis and molecular dynamics (MD) simulation studies of human Rab5a and its mutants have been extensively carried out. The effect of binding of a non-hydrolyzable GTP analog guanosine-5′-( β, γ )-imidotriphosphate (GppNHp) with Rab5a and its mutants are described. The objective of the current study is to perform a detailed examination of structural flexibility of Rab5a and its mutants p.Ala30Pro and p.Ala30Arg using MD simulations. Our observations suggest that mutant p.Ala30Arg stabilize the protein molecule when bound to GppNHp which offers additional contacts. Despite an in silico approach, this study provides a deep insight into the impact of mutation on the structure, function, stability, and mechanism of binding of GppNHp to the Rab5a at molecular level.